المناخ التنظيمي وأثره على الرضا الوظيفي وأداء الموظفين بمؤسسات التعليم العالي في سلطنة عمان - هنائي، سيف عبد الله سنان
The purpose of the current study is to identify the organizational climate and its effect to job satisfaction and the employees’ performance in the institutions of Higher Education in the Sultanate of Oman. To achieve the objective of the study, the researcher adopted the Descriptive Analytical Method and prepared a questionnaire of three parts: The reality of organizational climate, the reality of job satisfaction, as well as the reality of job performance. It was applied to a simple random sample of employees of Higher Education Institutions in North and South Batinah Governorates, in the Sultanate of Oman. The number of the random sample is (310) individuals. The study also included the statistical methods in data analysis: Cronbach's Alpha, Iterations, Arithmetic means, percentage and standard deviation of (SPSS- Statistical Package for the Social Science). The study concluded series of findings, the most significant: The higher level of the organizational climate, the higher level of the job satisfaction in higher education . institutions in Oman and vice versa. It is also clear, the higher level of the organizational climate, the higher level of the job performance in higher education institutions in Oman and vice versa. Based on the findings of the research, the researcher proposed a set of recommendations, the most important of which are: Greater attention to activate the communication system and cooperation between parts of the organizational structure. Increase attention to develop technology used in Higher Education Institutions. Further encourage and training the employees to carry out their work using the technology. Greater attention to the office environment for employees in terms of office designs (Ventilation, lighting and movement) and reformulating the performance evaluation criteria and the methods of its application in performance evaluation; In order to achieve a sense of security and job fairness. Pay more attention to employees’ motivation programs to motivate employees and rekindle their enthusiasm in serving their country and community, and striving to develop methods of achievement at work in accordance with quality standards of performance.